Intervenção em funções executivas, compreensão e metacompreensão de leitura em crianças com transtorno de déficit de atenção/hiperatividade - Fragoso, Analice Oliveira (2014)
The studies have investigated the association between attention deficit desorder and hyperactivity and deficits in executive functioning and reading. Consequently, the interventions are necessary in order to try to mitigate the impact of symptoms and difficulties generated by this association in people's lives. Thus, the aim of this study was to implement an intervention program for children with ADHD that promotes the development of their executive functions and reading, including comprehension skills and meta-understanding. The study was conducted with four participants aged between 7 and 14 years old, diagnosed with ADHD, duly enrolled in regular schools in the Greater São Paulo. The research was conducted in three phases. In the first, were administered to the children: Trail Making Test, Auditory and Visual Memory Working Test, Wisconsin Card Sorting, Attention Test for Cancellation, Meta-understanding Scale META Elementary I, Cloze Test and Cubes Subtests and the WISC-IV Vocabulary. Additionally, parents and teachers answered two surveys of executive functioning and regulation. In the second phase was conducted the intervention based on Early Intervention Program on. Executive Functioning (PIAFEx) and techniques to develop understanding and meta-understanding reading, in sessions with a pair of children, twice a week, over 1 year. In the third phase, all tests were reapplied. Quantitative descriptive analysis revealed that all subjects evolved in reading comprehension scores in most meta-understanding reading and some of the scores of executive functions. Quantitative analysis also suggested that the four subjects seem to have achieved improvements in the performance of tasks of executive functions, reading comprehension and meta-understanding. In application of Cloze test, for example, it was possible to realize an improvement of all subjects evaluated in the number of hits, both in the literal and in correction for meaning, which suggests that gained in relation to reading comprehension. The Attention Test for Cancellation, it was observed a tendency of increase in performance of three subjects evaluated. This trend was also observed for some subjects in other tests applied. Thus, in general the procedure seems to have been effective to promote advances in the performances of the participants, especially in tasks of meta-understanding and reading comprehension, but also in some activities of executive functions.